Coupling of local muscle deoxygenation and autonomic control depends on exercise intensity—insights from transfer entropy analysis. (7th December 2018) - Petelczyc, M; Bruhn, S; Weippert, M
Abstract: Objective : We analyzed the driving component between the periods of adjacent heartbeats (R–R intervals) and vastus lateralis-deoxygenation (%HHb) during incremental cycling. Considering a tight matching of local metabolism with systemic and local perfusion, a coupling between indices of cardiovascular control (R–R variability) and %HHb is suggested. Further, an intensity-dependent coupling between R–R variability and %HHb was hypothesized, because a multitude of feedback and feedforward mechanisms to autonomic cardiovascular control as well as local vasodilating mechanisms are associated with muscle metabolism and thus exercise intensity. Approach : Ten male triathletes (age: 34  ±  8 years) completed a test, including baseline (BAS, 50 W), a 25 W * min −1 ramp incremental phase until exhaustion and a recovery period (REC, 50 W). R–R intervals, %HHb and respiratory responses were simultaneously recorded. Five corresponding data segments were selected: BAS, before the first ventilatory threshold (preGET), between GET and the respiratory compensation point (preRCP), above RCP (postRCP), and REC. Bivariate transfer entropy (BTE) was applied to determine the signal coupling between R–R and %HHb. Main results : During preGET and preRCP, the analysis yielded the dominating direction from %HHb to R–R intervals, while for postRCP the direction was reversed. No significant signal coupling was detectable for the BAS and REC segments. Significance : Assuming that %HHb is related to the metabolic state of the working muscle, BTE results support the role of metaboreceptors in the systemic blood flow regulation at lower exercise intensities, while other mechanisms (e.g. baroreceptor and mechanoreceptor feedback, central command) that modulate cardiovascular control may override this coupling at higher intensities.